KOMITMEN MANAJEMEN, PENGETAHUAN K-3 & SIKAP K-3 DENGAN PENERAPAN SMK-3 PADA PEKERJA - Sidauruk, Silvana (Politeknik Kesehatan Kemenkes Bengkulu, 2014)
The application of sophisticated technology, machines, installations, and hazardous materials are increasing in relation to industrialization. These could facili-tate the production activities, however they could also give potential danger. This research is intended to identify the correlation and influence between commitment of management, the knowledge of safety, and attitude toward safety in regards to the implementation of OHS management system among the workers of PT. X Batam Shipyard Company. This is an analytical correlative research with a cross-sectional design. The research subjects are 63 persons, consist of supervisors and employees who work at the production division of PT. X Batam. The type of analy-sis used Pearson Product Moment Correlation and multiple regression tests. The result shows that there is a positively significant correlation and influence between commitment of management, the knowledge of safety, and attitude toward safety in regards to the implementation of OHS management system (R = 0651; p = 0.000), which has 42,4% contribution simultaneously. The result shows that commitment of management give the higher correlation and influence to the implementation of OHS management system (r=0,495; p=0,000), which has 22,13% contribution, followed by attitude toward safety (r=0,372; p=0,003) which has 12,17% contribution, and the knowledge of safety (r=0,321; p=0,010) which has 8,1% contribution.